2001
DOI: 10.2337/diabetes.50.5.937
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GSK-3 Selectively Reduces Glucose-6-Phosphatase and Phosphoenolpyruvate Carboxykinase Gene Expression

Abstract: A major action of insulin is to regulate the transcription rate of specific genes. The expression of these genes is dramatically altered in type 2 diabetes. For example, the expression of two hepatic genes, glucose-6-phosphatase and PEPCK, is normally inhibited by insulin, but in type 2 diabetes, their expression is insensitive to insulin. An agent that mimics the effect of insulin on the expression of these genes would reduce gluconeogenesis and hepatic glucose output, even in the presence of insulin resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
141
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(150 citation statements)
references
References 69 publications
9
141
0
Order By: Relevance
“…An assessment of the subcellular distribution of total and phosphorylated GSK-3 isoforms in neurons treated with various GSK-3 inhibitors is thus desirable to elucidate the underlying mechanisms and biological consequences in neurons following treatment with small molecule inhibitors. In addition, it has been reported that SB 216763 and SB 415286 cause a decrease in the phosphorylation levels of GSK-3␤ Ser 9 , an effect possibly medi- ated through their inhibition on p90 rsk2 , which directly phosphorylates GSK-3␤ Ser 9 (24,50). We also examined the effects of these two inhibitors in cultured cortical neurons and found similar results of reduced serine phosphorylation (supplemental Fig.…”
Section: Discussionsupporting
confidence: 63%
“…An assessment of the subcellular distribution of total and phosphorylated GSK-3 isoforms in neurons treated with various GSK-3 inhibitors is thus desirable to elucidate the underlying mechanisms and biological consequences in neurons following treatment with small molecule inhibitors. In addition, it has been reported that SB 216763 and SB 415286 cause a decrease in the phosphorylation levels of GSK-3␤ Ser 9 , an effect possibly medi- ated through their inhibition on p90 rsk2 , which directly phosphorylates GSK-3␤ Ser 9 (24,50). We also examined the effects of these two inhibitors in cultured cortical neurons and found similar results of reduced serine phosphorylation (supplemental Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Although it has been shown that overexpression of active Akt reduces PEPCK gene expression, this may be explained by inhibition of GSK3 (a physiological target of Akt) (40). Inhibitors of GSK3 strongly reduce PEPCK and G6Pase gene transcription in H4IIE cells (54). The data presented herein demonstrate that the regulation of IGFBP-1 gene transcription by insulin is affected by the presence of rapamycin, a treatment that does not affect insulin regulation of G6Pase (Fig.…”
Section: The Insulin Signaling Pathway That Regulates Igfbp-1 Gene Exmentioning
confidence: 63%
“…GSK3␤ plays regulatory roles in various diseases (21), including diabetes (22,23), Alzheimer disease (24,25), bipolar mood disorder (26), and cancer (27). GSK3␤ is also involved in innate and adaptive immune responses (28 -30).…”
Section: Discussionmentioning
confidence: 99%